Meaning gained versus meaning lost: The effects of meaning salience on anxiety and depression during the coronavirus pandemic. (16th June 2021) - Klussman, Kristine; Nichols, Austin Lee; Langer, Julia
Abstract : People who have meaningful lives generally experience less anxiety and depression. Meaning salience, or the awareness of the meaning in one's life, is believed to partially explain this relationship. However, in times of isolation, what might be most salient to people are the meaningful aspects of their lives that have disappeared. This study seeks to understand how making gained versus lost meaning salient affects anxiety and depression. Participants either wrote for 5 minutes about how their life gained meaning ( n = 29) or lost meaning ( n = 30) due to the coronavirus restrictions, or about music (i.e., the control condition; n = 32). Those who wrote about gained meaning experienced less momentary anxiety than those who wrote about lost meaning. In addition, meaning salience moderated the relationship between meaning and both anxiety and depression. Those who wrote about gained meaning appeared to exhibit a positive relationship between meaning in life (MIL) and both anxiety and depression, while those who wrote about lost meaning exhibited negative relationships. In all, this suggests that meaning salience is not always positive and that researchers and practitioners should consider how making positive meaning salient may be more beneficial than a general focus on MIL.